Calcium fertilizers induce soil suppressiveness to Phytophthora cinnamomi root rot of Quercus ilex - Serrano, María Socorro; Vita, Paolo; Fernández-Rebollo, Pilar; Sánchez Hernández, María Esperanza (European Journal of Plant Pathology, 2011)
t Based on the observation that the root disease caused by P. cinnamomi on Q. ilex has a low incidence and severity in soils with medium-high Ca 2+ content, we studied the ability of Ca 2+ fertilizers to induce soil suppressiveness to the pathogen. Studies on cultures of P. cinnamomi exposed to different Ca 2+ fertilizers in vitro showed significant inhibition of sporangial, chlamydospore and zoospore production at millimolar concentrations while mycelial growth was mainly unaffected. Experiments performed with artificially infested soil showed that some Ca 2+ fertilizers induce a significant decrease on chlamydospore viability. Additionally, greenhouse experiments using artificially infested soils showed a significant reduction of foliar and root symptom severities in Holm oak seedlings growing in soils amended with Ca 2+ fertilizers. We suggest that limestone amendments in oak rangelands could enhance the suppressiveness of soils to P. cinnamomi, and it is likely that the inhibition of sporangial production was the main mechanism involved.
Keywords: fertilization; limestone; Oak decline; Rangelands

Sustainability in Spanish Extensive Farms (Dehesas): An Economic and Management Indicator-Based Evaluation - Gaspar, P.; Mesías, F. J.; Escribano, M.; Pulido, F. (Rangeland Ecology & Management, 2009)
The dehesa is defined as an agroforestry system that is characteristic of the southwestern Iberian Peninsula, where grassland is combined with evergreen species of the genus Quercus. Those systems have been gradually transformed from the Mediterranean forest into a unique kind of pastoral woodland by means of an agricultural use. Dehesas occupy more than 6 million ha, and the livestock systems that are based in them are of vital importance for their sustainability. The present work classifies, describes, and evaluates the sustainability of these systems in the Spanish region of Extremadura (southwestern Spain). To this end, we apply a methodological adaptation of the Framework for the Evaluation of Management Systems incorporating Sustainability Index (MESMIS). MESMIS is based on the evaluation of basic attributes of sustainability from indicators that allow one to make a simultaneous and comparative analysis of different types of farms. For the study, 69 farms were selected at random, and were classified using multivariate techniques into four types according to their level of intensification and productive orientation. The results were used to obtain an overall value of sustainability from a technical economic perspective for each farm type present in the dehesa. The mixed systems (beef cattle–sheep–Iberian pigs) have been found to be the most sustainable in general terms. The high–stocking rate sheep dehesas are the least sustainable, although at present, they are the most profitable. The other two groups analyzed, “low–stocking rate sheep farms” and “beef cattle farms,” had intermediate and similar scores. Mixed livestock dehesa farms are the closest to the traditional systems with a highly diverse production, an optimal use of the system's resources, and little dependence on external subsidies. In the present context, with uncertainties about European Union subsidies, this type of farm should be a goal for dehesa farmers.
Keywords: livestock production; management strategies; MESMIS; Rangelands; Sustainability indicators

Using and comparing two nonparametric methods (CART and MARS) to model the potential distribution of gullies - Gutiérrez, Álvaro Gómez; Schnabel, Susanne; Lavado Contador, J. Francisco (Ecological Modelling, 2009)
Gully erosion represents an important soil degradation process in rangelands. In order to take preventive or control measures and to reduce its environmental damages and economical costs it is useful to localize the points in the landscape where gullying takes place and to determine the importance of the different factors involved. The study is carried out in Extremadura, southwest Spain. The main objectives of this work are: (a) comparing two nonparametric schemes to model the potential distribution of gullies, (b) evaluating the importance of the different factors involved in gullying processes, (c) analyzing the role of prevalence in the success of the model and ﬁnally, (d) implementing and mapping the results with the help of a Geographical Information System (GIS). Two methods were used to model the response of a dependent variable (gullying) from a set of independent variables: Classiﬁcation And Regression Trees (CART) and Multivariate Adaptive Regression Splines (MARS). Three different datasets were used; the ﬁrst one for constructing the model (training dataset) and the others for validating the model (external datasets). These datasets are formed by a target variable (presence or absence of gullies) and a set of independent variables. The dependent variable was obtained by mapping the locations of gullies with the help of a GPS and high resolution aerial ortophotographs. A set of 32 independent variables reﬂecting topography, lithology, soil type, climate, land use and vegetation cover of each area were used. The performance of the models was evaluated using a non-dependent threshold method: the Receiver Operating Characteristic (ROC) curve. The results showed a better performance of MARS for predicting gullying with areas under the ROC curve of 0.98 and 0.97 for the validation datasets, while CART presented values of 0.96 and 0.66.
Keywords: CART; Gully erosion; MARS; Nonparametric modelling; Rangelands; ROC curve